A replication study of the attitudes of selected academics and decision-makers towards adult students. - Curtis Smeby; Burton Sisco (Adult Education Research Conference, 1997)
The investigation examined the attitudes of selected academics and decision-makers towards adult students 15 years after the original study was conducted, in another rural state, and in another region of the United States. While the primary purpose was to replicate the original study, a secondary purpose was to compare and identify changes in attitude.